Protective Factors for Sexual and Gender Minoritized Youth - Oropeza, Olivia; Harris, Victor William (Advances in Social Sciences Research Journal, 2023)
Sexual and gender minoritized youth (SGMY) experience disproportionate rates of negative health and behavioral health outcomes relative to their heterosexual and cisgendered peers. Ample research has been dedicated to understanding the risk factors that may contribute to this disparity, however, less is understood regarding what protective factors may exist for this population. The purpose of this paper is to identify protective factors’ present throughout multiple levels of SGMY’s ecology and demonstrate how these protective factors may be important for the promotion of SGMY’s health and well-being. This paper utilizes multiple theories previously used to explore SGMY disparities, ultimately applying an adapted ecological systems framework to organize SGMY protective factors and their impacts. Application of this theoretical lens is vital to understanding the complex interaction of factors that influence SGMY development.